Moderate Consumption of Red Meat, Compared to Soy or Non-Soy Legume, Has No Adverse Effect on Cardio-Metabolic Factors in Patients with Type 2 Diabetes - Hassanzadeh-Rostami, Zahra; Hemmatdar, Zeinab; Pishdad, Gholam Reza; Faghih, Shiva (Experimental and Clinical Endocrinology & Diabetes, 2019)
Background Recently, it has been proposed that red meat consumption could enhance risk of diabetes and worsen lipid profile and glycemic status, in comparison with soy or non-soy legume, but the results of clinical trials are controversial.Objectives This study aimed to compare the effect of red meat, soy bean, and non-soy legume consumption on cardio-metabolic factors in patients with type 2 diabetes.Methods This was a randomized controlled clinical trial which included 75 patients with diabetes, aged 40–65 years. Participants were randomly allocated to receive two servings of red meat (control group), soy bean, or non-soy legume, 3 days a week for 8 weeks. All groups also received a balanced-macronutrients weight maintenance diet. Body composition and cardio-metabolic factors including fasting blood glucose (FBG), fasting insulin, glycated hemoglobin (HbA1c), serum lipids, and blood pressure were measured at baseline and endpoint of the study. Quantitative insulin sensitivity check index (QUICKI) score and Framingham risk score (FRS) were also computed.Results We found no significant differences in changes of FBG, fasting insulin, HbA1c, QUICKI score, serum lipids, FRS, and systolic and diastolic blood pressure among the 3 groups. Within group analysis showed that FRS reduced significantly in all groups (P<0.05). In addition, systolic (P=0.01) and diastolic (P=0.03) blood pressure reduced within red meat group.Conclusions Compared to soy bean or non-soy legume, moderate consumption of red meat had no adverse effect on cardio-metabolic factors including FBG, fasting insulin, HbA1C, QUICKI score, total cholesterol, low-density lipoprotein , high-density lipoprotein , and blood pressure in adults with type 2 diabetes.
Keywords: type 2 diabetes; cardiometabolic risk factors; non soy legumes